2012
DOI: 10.1039/c2cc30384a
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymers and aptamers mediated aggregation of gold nanoparticles for the colorimetric detection of arsenic(iii) in aqueous solution

Abstract: As(III) specifically interacts with an arsenic-binding aptamer to form an As(III)-aptamer complex, so that the following cationic polymer can aggregate gold nanoparticles (AuNPs) and cause a remarkable change in color, which enables the colorimetric detection of As(III) with high selectivity and a detection limit of 5.3 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(116 citation statements)
references
References 19 publications
3
113
0
Order By: Relevance
“…Inorganic As contamination is a pressing environmental issue that causes a serious threat to human health. 16 MG is a cationic dye that is widely used as an antiseptic in the aquaculture industry, but it is suspected of being genotoxic and carcinogenic. 17,18 Recent studies showed that SERS is a promising technique for rapid detection of MG [19][20][21][22] and As(v), [23][24][25][26] but the method sensitivity and selectivity require further improvement, and a fast, highly efficient and low-cost procedure for preparation of SERS substrates is urgently needed.…”
mentioning
confidence: 99%
“…Inorganic As contamination is a pressing environmental issue that causes a serious threat to human health. 16 MG is a cationic dye that is widely used as an antiseptic in the aquaculture industry, but it is suspected of being genotoxic and carcinogenic. 17,18 Recent studies showed that SERS is a promising technique for rapid detection of MG [19][20][21][22] and As(v), [23][24][25][26] but the method sensitivity and selectivity require further improvement, and a fast, highly efficient and low-cost procedure for preparation of SERS substrates is urgently needed.…”
mentioning
confidence: 99%
“…Noble metal nanomaterials (e.g., Au and Ag) have been commonly used to develop highly sensitive colorimetric probes for the determination of biomolecules 21,22 , drugs 23 , toxicants [24][25][26][27][28] and small molecules [29][30][31] due to their optical and electrical properties and biocompatibility 32,33 . Ag nano materials are more cost effective in their preparation than Au nano materials.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticles are stabilized by the adsorbed oligonucleotides at high salt concentration, and aggregated when the target is present, leading to a change in colour. However, the high assembly time of the above assay coupled with relatively poor (low nano-molar) detection limits using salts prompted the use of other ionic agents like conjugated polyelectrolytes [10], cationic polymers [11] and cationic surfactants [12] instead of salt, for the development of AuNP aggregation-based detection assays.…”
Section: Introductionmentioning
confidence: 99%